PENURUNAN KADAR Fe DAN Mn PADA AIR SUMUR GALI DENGAN AERASI GELEMBUNG UDARA DI DESA SIDING KECAMATAN BANCAR KABUPATEN TUBAN - Trisetyani, Indarti; Sutrisno, Joko (WAKTU, 2014)
Wells water in the village of Siding, Bancar, Tuban contains Fe and Mn more thanmaximum limit allowed by the health minister number 416/Menkes/PER/IX/1990, for level of Fe inthe clean water should not be more than 1,0 mg/l and Mn 0,5 mg/l. This research aims to reducethe content of Fe and Mn in wells water with bubbles aeration so that will meet quality standards ofclean water, to find the length of time and effective aeration and decreased Fe and Mn fromtreatment with bubbles aeration. The research is done using a plastic tub of aeration, air supply isdone by pumping water size 17 w and nozle size 1,5 mm by the time variation 20, 40 and 60minutes. Sampling was performed 3 times for each treatment, than analyzed in the laboratory toknow the decrease levels of Fe and Mn. The results of research showed that the levels of Fe andMn were high in well water very good to treatment by bubbles aeration. The beginning of level Fe3,1 mg/l and Mn 0,87 mg/l, after aerated Fe level in water is 0,0037 mg/l and Mn 0,0491 mg/l (appropriate water quality standards). Average decreased of Fe content after the bubbles aeratedfrom 20 minutes at 90 %, 40 minutes at 96 %, 60 minutes at 95 % and Mn content after aerated for20 minutes decreased 51 %, 40 minutes 54 %, 60 minutes 75 %.